Recombinant full-length Bacillus Anthracis protective antigen and its 63 kDa form elicits protective response in formulation with addavax - Sharma, Shikhar; Bahl, Vanndita; Srivastava, Gaurav; Shamim, Risha; Bhatnagar, Rakesh; Gaur, Deepak (Frontiers in Immunology, 2023)
Bacillus anthracis is the causative agent for the lethal disease anthrax, primarily affecting animals and humans in close contact with an infected host. The pathogenicity of B. anthracis is attributed to the secreted exotoxins and their outer capsule. The host cell-binding toxin component “protective antigen” (PA) is reported to be a potent vaccine candidate. In the current study, we have designed the various subunit, protective antigen-based recombinant proteins, i.e., full-length Protective antigen (PA-FL), C-terminal 63 kDa fragment (PA63), Protective antigen domain 1-domain 4 chimeras (PA-D1-4) and protective antigen domain 4 (PA-D4) and analyzed their vaccine potential with different human-compatible adjuvants in the mouse model. We have optimized the process and successfully expressed our recombinant antigens as soluble proteins, except full-length PA. All the recombinant antigen formulations with three different adjuvants i.e., Addavax, Alhydrogel, and Montanide ISA 720, were immunized in different mouse groups. The vaccine efficacy of the formulations was analyzed by mouse serum antigen-specific antibody titer, toxin neutralization assay, and survival analysis of mouse groups challenged with a lethal dose of B. anthracis virulent spores. The results from our study have determined that the PA-FL addavax and PA63 addavax formulations were most effective in protecting spore-challenged mice and serum from the mice immunized with PA-FL addavax, PA-FL alhydrogel, PA63 addavax, and PA63 alhydrogel formulations were equivalently efficient in neutralizing the killing effect of anthrax lethal toxin. The higher levels of serum Th1, Th2, and Th17 cytokines in PA-FL addavax immunized mice correspond to the enhanced protection provided by the formulation in challenged mice. In the present study, we have demonstrated that the PA-FL addavax and PA63 addavax formulations exhibit equivalent efficiency as vaccine formulation both in a mouse model of anthrax and mammalian cell lines. However, PA63 is a smaller antigen than PA-FL and more importantly, PA63 is expressed as a soluble protein in E. coli, which imparts a translational advantage to PA63-based formulation. Thus, the outcome of our study has significant implications for the development of protective antigen-based vaccine formulations for human use against the lethal disease anthrax.